Influence of Temperature on the Effects of Water Stress on Quercus Species - SPYROPOULOS, C G; LAMBIRIS, M P (Annals of Botany, 1979)
Quercus coccifera L. and Q. ilex L. leaves, collected in winter, when the plants were in full turgor, were treated with polyethylene glycol (PEG) with a water potential of −48 and −65 bar, at 15 °C and at 30 °C, for 2 days. The response of each species differs with temperature as far as the plastid pigment, anthocyanin and soluble sugar content is concerned. Thus Q. ilex is affected more at 15 °C rather than at 30 °C, while in Q. coccifera, apart from a small increase in anthocyanins, no significant change was observed at 15 °C. On the contrary, at 30 °C significant changes were observed in all studied parameters. Chloroplast pigments decreased generally on the first day and their content either dropped further or increased to reach the control values on the second day. All treatments resulted in an increase in anthocyanin content. Soluble sugar content raised in Q. ilex at 15 °C and decreased in both species at 30 °C.
Keywords: anthocyanin; carotenoids; chlorophyll; oak; Quercus coccifera; Quercus ilex; Temperature; water stress